A pig multi-tissue normalised cDNA library: large-scale sequencing, cluster analysis and 9K micro-array resource generation - Soares Marcelo B; Bonaldo Maria F; Benne Francis; Hugot Karine; Iannuccelli Eddie; Bonnet Agnès; Hatey François; Tosser-Klopp Gwenola (BMC Genomics, 2008)
Abstract Background Domestic animal breeding and product quality improvement require the control of reproduction, nutrition, health and welfare in these animals. It is thus necessary to improve our knowledge of the major physiological functions and their interactions. This would be greatly enhanced by the availability of expressed gene sequences in the databases and by cDNA arrays allowing the transcriptome analysis of any function. The objective within the AGENAE French program was to initiate a high-throughput cDNA sequencing program of a 38-tissue normalised library and generate a diverse microarray for transcriptome analysis in pig species. Results We constructed a multi-tissue cDNA library, which was normalised and subtracted to reduce the redundancy of the clones. Expressed Sequence Tags were produced and 24449 high-quality sequences were released in EMBL database. The assembly of all the public ESTs (available through SIGENAE website) resulted in 40786 contigs and 54653 singletons. At least one Agenae sequence is present in 11969 contigs (12.5%) and in 9291 of the deeper-than-one-contigs (22.8%). Sequence analysis showed that both normalisation and subtraction processes were successful and that the initial tissue complexity was maintained in the final libraries. A 9K nylon cDNA microarray was produced and is available through CRB-GADIE. It will allow high sensitivity transcriptome analyses in pigs. Conclusion In the present work, a pig multi-tissue cDNA library was constructed and a 9K cDNA microarray designed. It contributes to the Expressed Sequence Tags pig data, and offers a valuable tool for transcriptome analysis.